2007
DOI: 10.1111/j.1526-4610.2006.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Thunderclap Headache Caused by Minimally Invasive Medical Procedures: Description of 2 Cases

Abstract: We report 2 very unusual cases of thunderclap headache complicating minimally invasive medical procedures. In the first case headache developed as the consequence of a pneumocephalus caused by an inadvertent intrathecal puncture during oxygen-ozone therapy for lumbar disk herniation. The second case involved intracranial hypotension, caused by the persistence of the needle, used for epidural anesthesia, and then penetrated in the subarachnoid space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…There are isolated case reports involving adverse events following intradiscal injection of ozone. These include a case of transient bilateral blindness following injection of a large volume of ozone to the disc without radiographic control, 43 a nerve root injury associated with a pressure spike during the injection, 44 a thunderclap headache attributed to puncture of the thecal sac, 45 a severe case of discitis requiring revision surgery, 46 and a fatal septicemia due to E. Coli infection. 47 Two meta-analysis of intradiscal ozone have been published and both concluded that intradiscal ozone injection is both safe and effective in patients with disc herniation.…”
Section: Introductionmentioning
confidence: 99%
“…There are isolated case reports involving adverse events following intradiscal injection of ozone. These include a case of transient bilateral blindness following injection of a large volume of ozone to the disc without radiographic control, 43 a nerve root injury associated with a pressure spike during the injection, 44 a thunderclap headache attributed to puncture of the thecal sac, 45 a severe case of discitis requiring revision surgery, 46 and a fatal septicemia due to E. Coli infection. 47 Two meta-analysis of intradiscal ozone have been published and both concluded that intradiscal ozone injection is both safe and effective in patients with disc herniation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Devetag Chalaupka et al . [ 3 ] reported a 27-year-old man as the first case of a severe headache due to pneumocephalus after epidural puncture of oxygen-ozone therapy. In this case, the symptom of a thunderclap headache and the image findings of pneumocephalus were similar to those reported by Devetag Chalaupka et al .…”
mentioning
confidence: 99%
“…In this case, the symptom of a thunderclap headache and the image findings of pneumocephalus were similar to those reported by Devetag Chalaupka et al . [ 3 ] Fortunately, both cases of thunderclap headache second to pneumocephalus (oxygen-ozone gas) resolved with no further symptoms. Physicians should be aware of this potential complication of minimally invasive oxygen-ozone therapy and be prepared to diagnose and treat this complication.…”
mentioning
confidence: 99%
“…Previous studies have also shown that a thunderclap headache is caused by an inadvertent intrathecal puncture during oxygen–ozone therapy for lumbar disk herniation. 13 However, in our cohort, no patients reported this complication not only during the procedure but also in subsequent days.…”
Section: Methodsmentioning
confidence: 55%